Training on the cultivation technique of indigofera plants and introduction to drones for the world of agriculture and forestry [Pelatihan teknik budidaya tanaman indigofera dan pengenalan drone untuk dunia pertanian dan kehutanan] - Saijo, S; Iskandar, Beni; Susilo, Djoko Eko Hadi (Universitas Syiah Kuala, 2025)
The productivity of ruminant livestock is closely correlated with the continuous availability of forage, both in quality and quantity, making its availability crucial. On the other hand, the use of drone technology to support efforts in agriculture and forestry is also very important to be socialized to the community. Therefore, training is the right solution to achieve this, enabling the dissemination of knowledge about the utilization of indigofera as livestock feed and the use of drones. The aim of this service is to train students on indigofera cultivation techniques and how to use drones in the fields of agriculture and forestry. The service is conducted at Senior High School 1 Jabiren Raya, Jabiren Raya Sub-District, Pulang Pisau District, Central Kalimantan Province, using a training method, with 40 students participating. It will be held on February 18, 2025, with several stages of preparation and implementation. Activities were conducted at two locations, the first in the Auditorium with a theoretical presentation, and the second on the grounds of SMAN 1 Jabiren Raya, which served as a practical site for cultivation and drone operation. The results of the community service activities indicate that the training on indigofera cultivation techniques and the introduction of drone usage in agriculture and forestry showed a significant difference in knowledge before and after the training. In conclusion, the comparison of understanding before and after the training was 27% compared to 90%.